Ecological trap for Cnemidophorus ocellifer Spix 1825 (Squamata: Teiidae) during removal of vegetation - Lucas Bezerra Brito; Igor Joventino Roberto; Paulo Cascon (Biotemas)
Animals must anticipate future conditions according to current environmental clues. When habitats are rapidly modified, these signs may not reflect the actual environmental quality, leading to a decreased fitness of an individual and its population. During an activity of faunal rescue and scaring away in the coast of Rio Grande do Norte, Brazil, evidence of an ecological trap for the lizard Cnemidophorus ocellifer was observed. We suggest some actions which can minimize the impact of vegetation removal activities on lizards, such as: i) better planning before proceeding with deforestation; and ii) capture and release of lizards in appropriate locations.